The role of ClpP, RpoS and CsrA in growth and filament formation of Salmonella enterica serovar Typhimurium at low temperature - Knudsen, Gitte Maegaard (BMC Microbiol, 2014)
BACKGROUND: Salmonellae are food-borne pathogens of great health and economic importance. To pose a threat to humans, Salmonellae normally have to cope with a series of stressful conditions in the food chain, including low temperature. In the current study, we evaluated the importance of the Clp proteolytic complex and the carbon starvation protein, CsrA, for the ability of Salmonella Typhimurium to grow at low temperature. RESULTS: A clpP mutant was severely affected in growth and formed pin point colonies at 10°C. Contrary to this, rpoS and clpP/rpoS mutants were only slightly affected. The clpP mutant formed cold resistant suppressor mutants at a frequency of 2.5 × 10(−3) and these were found not to express RpoS. Together these results indicated that the impaired growth of the clpP mutant was caused by high level of RpoS. Evaluation by microscopy of the clpP mutant revealed that it formed filamentous cells when grown at 10°C, and this phenotype too, disappered when rpoS was mutated in parallel indicating a RpoS-dependency. A csrA (sup) mutant was also growth attenuated a low temperature. An rpoS/csrA (sup) double mutant was also growth attenuated, indicating that the phenotype of the csrA mutant was independent from RpoS. CONCLUSIONS: The cold sensitivity of clpP mutant was associated with increased levels of RpoS and probably caused by toxic levels of RpoS. Although a csrA mutant also accumulated high level of RpoS, growth impairment caused by lack of csrA was not related to RpoS levels in a similar way.